Issue Cover. (27th September 2021) - Flores‐Guerrero, Jose L.; Post, Adrian; van Dijk, Peter R.; Connelly, Margery A.; Garcia, Erwin; Navis, Gerjan; Bakker, Stephan J. L.; Dullaart, Robin P. F.
Abstract : The cover image is based on the Original Article Circulating trimethylamine‐N‐oxide is associated with all‐cause mortality in subjects with nonalcoholic fatty liver disease by Jose L. Flores‐Guerrero et al., https://doi.org/10.1111/liv.14963 .